Pengaruh Modal Kerja dan Kinerja Keuangan Terhadap Harga Saham - Pangesthu, Nilman Indrha; Aprilia, Erika Astriani (JURNAL PUNDI, 2025)
This research aims to determine the effect of working capital and financial performance on share prices in LQ45 sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling method in this research used purposive sampling, so that a research sample of 16 companies was obtained. Data analysis was carried out using the panel data regression method using eviews 9. Simultaneously working capital and financial performance had effect on stock prices. Partially, working capital has no effect on share prices, financial performance as a proxy for profitability has an effect on stock prices, and financial performance with a proxy for liquidity has no effect on stock prices.